From Rationality to Reality: A Systematic Synthesis of Behavioral Biases and Irrationality in Global Real Estate Markets - Muhammad Sahlan; Eko Susanto (Integrasi Sains Media, 2025)
The traditional paradigm of real estate finance is currently undergoing a fundamental transition from neoclassical